Fostering Extensive Reading Comprehension through the Medium of Let’s Read” Application - Destiara, Elmeyra Bethany; Mutiarani (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
The aim of this study was to measure the effectiveness of “Let’s Read”application in fostering students’ Extensive Reading comprehension. Two classess of grade 8 students of SMP Muhammadiyah 03 Tangerang participated as the sample of this study, divided into experimental class and control class each of which was occupied by 34 students. These two classes were chosen by using cluster random sampling out of totally 4 classes of grade 8. This quantitative research used quasi-experimental with two-groups post-test only design. The data were gathered by using Reading Comprehension post-test and a questionnaire. All collected data of the post-test were analyzed statistically by using independent t-test. The analysis of the findings revealed that experimental group students’ post-test achievement exceeded 12.5 points the achievement of control gorup students’. Meanwile, in the statistical analysis, in the significance level of 5% ( = 5% degree of freedom), t-obtained of 5.677 was higher than t-table of 1.996 (from df = 66). Besides, the table also showed that the sig. (2-tailed) of 0.000 < 0.05. Therefore, Ha was accepted and H0 was rejected. Experimental group students’ responses to the questionnaire showed that the majority of them expressed that Let’s Read application benefitted them in the activities of extensive reading practices in which foe example their reading interest increased after learning reading through this app. Based on these findings, this study concluded that Let’s Read application was an effective learning medium in fostering students’ extensive reading comprehension.